SOCIAL PRACTICES UNDERLYING A-MILD SAMPOERNA CIGARETTE’S ADVERTISEMENTS: “BUKAN MAIN” EDITION - Mahajendra, Pande Gede Baba; Dewi, Iga Lokita Purnamika Utami; Ramendra, Dewa Putu (Universitas Muhammadiyah Metro, 2024)
As one of the subjects of discourse analysis, advertising contains a wide variety of exciting topics that can be discussed. The advertisement for the cigarette, which emphasizes the impact on one’s emotions, also provides an opportunity for reflective thought. The purpose of this article was to explain the advertisement for A-Mild Sampoerna Cigarettes that appeared in the Bukan Main Edition concerning the social practices component. The research utilized Fairclough’s Critical Discourse Analysis framework, following the qualitative methodology. The primary and secondary data comprised five advertisements from the A-Mild Sampoerna advertisement Bukan Main Edition and relevant literature in the shape of articles and books. A cycle consisting of data collection, condensation, data triangulation, and conclusion drawing was created because of the deductive method of data collection and analysis used. The findings reveal some fascinating results regarding the impact of the company’s advertisements on society. The analysis results also showed that the theme of the advertisement chosen by the company picturized the social issues that occurred in daily life in Indonesia, which is covered through the arrangement of discursive phrases. Implications were drawn concerning enhancing analytical skills, raising social consciousness, forming critical thinking, and the occupation of references surrounding the investigated problem.